Use of Cefoperazone MacConkey Agar for Selective Isolation of Laribacter hongkongensis - Lau, Susanna K. P. (American Society for Microbiology, 2003)
A new selective medium, cefoperazone MacConkey agar (CMA), was developed for primary isolation of Laribacter hongkongensis from stool. Its performance in quantitative recovery and in a clinical evaluation of 4,741 human diarrheal stool specimens was superior to that of charcoal cefoperazone deoxycholate agar. In addition, with CMA, Arcobacter butzleri was unexpectedly isolated from the stools of six patients.